Advanced hawkes processes for practical event sequence analysis : models and accelerations - Li, Tianbo (Nanyang Technological University, 2021)
Hawkes processes, first proposed in the name of self- and mutually exciting point process, have been widely used to model event sequences produced from natural and social systems. Hawkes processes can capture both individual and interactive behaviors and have achieved satisfactory results in a variety of disciplines. Ranging from recommender systems to earthquake prediction to neural activities, applications regarding Hawkes process have confirmed the effectiveness of the model as a competent tool for dealing with event sequences. In this thesis, I specifically focus on the extension of Hawkes processes to practical event sequences analysis. In particular, I make efforts to the study of Hawkes processes in two aspects: modeling and algorithm acceleration.